PELATIHAN MICROSOFT WORD SEBAGAI MEDIA AWAL PENGUATAN LITERASI DIGITAL UNTUK PENGEMBANGAN WEB DASAR BAGI SISWA SMA IBRAHIMY 2 SUKOREJO - Alfina Damayanti; Ratu Maulidia Anggraini; Zaehol Fatah (Jurnal Padamu Negeri, 2025)
This training aims to introduce the use of Microsoft Word as an initial medium for strengthening digital literacy in the context of basic web development for high school students. This activity is motivated by the limited facilities at SMA Ibrahimy 2, which until now does not have a computer laboratory or optimal access to information and computer technology (ICT) learning. Through a training method based on direct practice and a qualitative approach, students are guided to create Word documents. And convert it into HTML format which is then uploaded to GitHub and published as a web page via GitHub Pages. The results of the training show that students are able to follow each stage, starting from writing content, inserting image media, to the web publication process independently.